Structural characterization, antioxidant activity and anti-inflammatory of the phosphorylated polysaccharide from Pholiota nameko - Zhang, Xu; Liu, Tingting; Wang, Xi; Zhou, Lanying; Qi, Ji; An, Siyu (Frontiers in Nutrition, 2022)
In this study, a novel polysaccharide (SPN) was extracted by high-temperature pressure method and purified by a DEAE-52 column and a Sephadx G-100 gel column. PPN was obtained after phosphorylation of SPN. The differences of structural features, antioxidant activity, and anti-inflammatory effect of the two polysaccharides were investigated by chemical methods and RAW 264.7 cell model. SPN (Mw = 15.8 kDa) and PPN (Mw = 27.7 kDa) are an acidic polysaccharide with β-pyranose configuration, mainly containing rhamnose, mannose, glucose, arabinose, and galacose. FI-IR, NMR, and SEM spectra showed phosphorylation of SPN changed its structure. In methylation analysis, the major chains of SPN and PPN were 1,4-linked Glcp, 1,6-linked Galp, 1,2-linked Rhap, and 1.6-linked Manp with terminals of t-linked Glcp, t-linked Araf. The side chain of SPN was 1,4,6-linked Galp, 1,2,5-linked Araf, while the side chain of PPN was 1,4,6-linked Galp, 1,2,4-linked Glcp. In antioxidant activity experiments, the free radical scavenging rate of PPN was stronger than that of SPN. Also, PPN always has better anti-inflammatory on RAW 264.7 cells induced by LPS than that of SPN in same concentration, and it plays an anti-inflammatory role by inhibiting PI3K/AKT/mTOR pathway. The results indicated polysaccharide could significantly improve its antioxidant and anti-inflammatory function after phosphorylation. This study provides a potentially antioxidant and anti-inflammatory health food and drug.